A CONTEXTUAL ANALYSIS OF BIOMETRIC ATTENDANCE SYSTEMS FOR HEALTHCARE EMPLOYEES IN PUNJAB - Ali, Zulfiqar; Saeed, Amir; Sami, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
History of health sector reforms in Punjab, Pakistan is strewn with initiatives based on exogenous culture e.g., NPM to bring about efficiency and effectiveness in the public sector. Biometric attendance System for healthcare employees in Punjab is in line with the trajectory of reforms, based on foreign cultural ideals, under the garb of technology without taking into account the contextual realities. This paper, by using the interpretive methodology, seeks to study the phenomenon of Biometric Attendance System in light of Western cultural ideals e.g., instrumental perspective, modernity, liberal individualism, and autonomy and conclude that such technological solutions are ahistorical and atemporal.